2022
DOI: 10.3390/toxins14070471
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fumonisin B1 on Proliferation and Apoptosis of Intestinal Porcine Epithelial Cells

Abstract: Fumonisin B1 (FB1), which is a mycotoxin produced by Fusarium moniliforme and Fusarium rotarum, has a number of toxic effects in animals. Moldy feed containing FB1 can damage the intestine. In this study, we used intestinal porcine epithelial cells (IPEC-J2) as an in vitro model to explore the effects of FB1 on cell cycle and apoptosis. The results showed that IPEC-J2 cells treated with 10, 20, and 40 μg/mL FB1 for 48 h experienced different degrees of damage manifested as decreases in cell number and viabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…Previous results showed that FB1 exposure in human gastric epithelial (GES-1), kidney tubular epithelial (HK-2), and monkey kidney (MARC-145) cells caused cytotoxicity and cell death [29][30][31], while FB1 in human liver hepatoblastoma (HepG2) cells led to oxidative stress [32]. FB1 could also induce cytotoxicity proliferation inhibition and promote cell death in IPEC-J2 cells from the porcine intestine [33]. Consistent with these reported results, this study also revealed that FB1 could dose-and time-dependently exert cytotoxicity on IEC-6 cells, causing growth inhibition and MMP loss, promoting LDH release, and enhancing ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…Previous results showed that FB1 exposure in human gastric epithelial (GES-1), kidney tubular epithelial (HK-2), and monkey kidney (MARC-145) cells caused cytotoxicity and cell death [29][30][31], while FB1 in human liver hepatoblastoma (HepG2) cells led to oxidative stress [32]. FB1 could also induce cytotoxicity proliferation inhibition and promote cell death in IPEC-J2 cells from the porcine intestine [33]. Consistent with these reported results, this study also revealed that FB1 could dose-and time-dependently exert cytotoxicity on IEC-6 cells, causing growth inhibition and MMP loss, promoting LDH release, and enhancing ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Fusarium mycotoxins deoxynivalenol (DON) and fumonisin B1 (FB1) have been reported to directly affect the viability of phagocytic cells such as macrophages. Moreover, these mycotoxins can induce cellular apoptosis, inhibit proliferation, and impair the function of epithelial cells in vitro and in vivo [4,5], and can affect the expression of cytokines and chemokines, leading to immunosuppression and increased susceptibility to infections [6]. Several mycotoxins are also able to modulate the production of cytokines in different organs and/or cell types [7,8].…”
Section: Introductionmentioning
confidence: 99%